Ion beam modification of polyethylene and adhesion to epoxy adhesive - Mesyats G. A. Gennady Andreyevich; Klyachkin Yu. S.; Gavrilov N. V.; Mizgulin V. N.; Yakushev R. M.; Kondyurin A. V. (1996, 1996)
В фонде НТБ ТПУ отсутствует